STO: Equity Crowdfunding Innovation for Indonesian Start-Up - Clara Valentine Febiolla; Erinne Yeolencia; Rimba, Samantha Meidelin Lavenda (KINERJA, 2022)
Blockchain and crowdfunding are innovations that have brought significant changes to business and funding activities around the world. The existence of blockchain has created cryptocurrency, which is currently popular among many investors worldwide, without exception for domestic investors. On the other hand, crowdfunding tools such as equity crowdfunding could develop a blockchain-based funding system. This system uses a cryptocurrency security token as an investment instrument, where the initial offering is referred as a Security Token Offering (STO). This study aims to analyse a blockchain-based equity crowdfunding system using cryptocurrency security tokens and design the system for start-up companies in Indonesia. This study used a descriptive method with qualitative approach used SWOT analysis and quantitative approach with questionnaire as supporting data. This study indicates that the existence of blockchain-based equity crowdfunding provides opportunities for start-ups in Indonesia to obtain funds for developing their business. Keywords: blockchain, crowdfunding, cryptocurrency, start-up company, security token offering